Consideration of Events, Measures and Reasons of Disaster in Himalaya: Exploring disaster events and measures in the Himalaya region for sustainable development (Journal of Advances and Scholarly Researches in Allied Education, 2019)
A disaster is characterized as the result of a hazard contrarily affecting a social ecological framework. The magnitude of the disaster is straightforwardly related with the force of the hazard just as with the introduction and the powerlessness of the social-ecological framework. In any case, the disasters could be evaluated from multiple points of view number of deaths, number of structures fallen, kilometers of roads wrecked, cash misfortune because of the disturbance of financial exercises. Disasters frequently invalidate the endeavors and diligent work of quite a long while in merely hours and even minutes and seconds. Disasters can be seen as a progression of stages on a period continuum. Despite the fact that the advancing circumstance may seem ceaseless, recognizing and understanding these stages portrays related necessities and to conceptualize suitable disaster management exercises. The territory crushed by sad on first July 2016 is situated in Didihat and Thal Tehsils of Pithoragarh district and fall in the catchments of East Ramganga and Charma waterways individually. Heavy rains caused landslide incidences and harms in the territory around Didihat, Bastari and Naulra towns. Upwards of 21 human lives were lost in these incidences. The effect on these areas of landslides brought about by heavy rainfall occasions and quick changes in scene. Landslide incidences are credited to development on free soiloverburden material and drainages. Expanding anthropogenic exercises, wandering in hazardous regions because of constrained land accessibility and heavy confined precipitation. These are constantly expanding the weakness of these to landslides. In perspective on that, the paper will give experiences into suggestive measures that may help in setting up a roadmap towards sustainable development inside the influenced territories.